Trichoptera of Mindoro, the Philippines I. New species and records from the Baroc River Catchment, Roxas, Oriental Mindoro (Insecta, Trichoptera) - Freitag, Hendrik (Archīum Ateneo, 2013)
The study of a collection of caddisflies from Mindoro yielded a total of 34 species. Eight species proved to be unknown taxa and are described in the present article as: Rhyacophila crenophysetis spec. nov., Agapetus parallelaria spec. nov., Stactobia roxasi spec. nov., Paduniella vicentis spec. nov., Paduniella prodita spec. nov., Psychomyia taugadensis spec. nov., Tinodes hypoplectis spec. nov., and Ecnomus biundularia spec. nov. A list of all collected species is provided.